Institutional learning and knowledge transfer across epistemic communities : new tools of global governance - Carayannis, Elias G. (Innovation, Technology, and Knowledge Management, 2012)
Over the past several decades, as the pace of globalization has accelerated, operational issues of international coordination have often been overlooked.  For example, the global financial crisis that began in 2007 is attributed, in part, to a lack of regulatory oversight.  As a result, supranational organizations, such as the G-20, the World Bank, and the International Monetary Fund, have prioritized strengthening of the international financial architecture and providing opportunities for dialogue on national policies, international co-operation, and international financial institutions. Prevailing characteristics of the global economic systems, such as the increasing power of financial institutions, changes in the structure of global production, decline in the authority of nation-states over their national economy, and  creation of global institutional setting, e.g., global governance have created the conditions for a naturally evolving process towards enabling national epistemic communities to create institutions that comply with global rules and regulations can control crises.  In this volume, the authors provide in-depth analysis of initiatives to demonstrate how this type of knowledge generated at the international organization level, is codified into global standards, and disseminated to members, particularly in the developing world, where the legal and regulatory infrastructure is often lacking.  They argue that despite the challenges, when a country intends to join the global system, its institutions and economic structures need to move toward the global norms.  In so doing, they shed new light on the dynamics of knowledge transfer, financial regulation, economic development, with particular respect to supporting global standards and avoiding future crises.